(untitled) (Global Economic Review: Journal of Economics, Policy, and Business Development, 2025)
This article analyzes the role of domestic investments and foreign direct investments (FDI) in the economy of Uzbekistan and their distribution by sector. The reforms implemented in the country to improve the investment climate, the dynamics of investment flows and their ratio to gross domestic product (GDP) are highlighted, as well as economic efficiency indicators. The contribution of FDI to technological innovation, the introduction of modern management systems, and the creation of new jobs is also shown based on numerical analysis. The economic activity of domestic investors and financial support measures provided by the state are also studied in detail.